CRITICISM OF THE IMPLEMENTATION OF K3 CULTURE IN THE WORKPLACE ACCORDING TO THE LAW IN INDONESIA - Andi Lala (Faculty of Law, Universitas Pekalongan, 2024)
Occupational safety and health for workers are paramount, as workers are a means of production that must be fulfilled for their K3 rights. One of them is how the K3 culture that companies must implement and socialize with all workers. In writing this journal, the author uses a qualitative methodology with a normative approach and literature study, which can then be called doctrinal research. A literature study identified literature in laws and regulations, books, papers, journals, and other sources related to this research. The study results in this journal show that the author can conclude that implementing K3culture in the workplace at this time, especially in Indonesia, still needs to be considered fully implemented. Even in all the rules that discuss K3, the principles of implementing K3 culture have yet to be emphasized, even though K3 culture is essential in carrying out every job in every work sector.